Upaya Perlindungan Hukum Terhadap Hak Kesehatan Jasmani Pasien Gangguan Jiwa Berat di Indonesia - Silvester Anang Prananto Timur; Lego Karjoko; Fatma Ulfatun Najicha (PLEDOI (Jurnal Hukum dan Keadilan), 2023)
Often with the development of national development which is in line with the 1945 Constitution, the health sector is one part of the national development that the government is trying to achieve the degree of health. Which as high as possible. To guarantee the right to health for every Indonesian citizen, the arrangement is legal protection that is certain for the people in seeking justice. In this regard, the legal issues that occur in Indonesia concern the right to health for people with severe mental disorders who are often underestimated in society and receive a negative stigma that hinders the fulfillment of their right to health. In this case, patients with psychiatric disorders do not only have problems in the psychological sphere but can also have problems in the physical (physical) sphere. This study aims to analyze legal protection for fulfilling the physical health rights of patients with severe mental disorders in Indonesia using normative research methods by collecting legal material sources through positive law legislation and other legal sources of literature to answer the problem solving of these legal issues as a whole. prescriptive. From a review of the regulations of Law no. 36 of 2009 concerning Health found that the right to health is an equal right for all Indonesian citizens, and the services provided are anti-discrimination. In accordance with Law no. 44 of 2009 concerning Hospitals, hospitals have an obligation to provide services and care for patients both medically and non-medically by implementing a referral system according to hospital classification.